2020
DOI: 10.21203/rs.2.19479/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethylene glycol and glycolic acid production from xylonic acid by Enterobacter cloacae

Abstract: Background: Biological routes for ethylene glycol production have been developed in recent years by constructing the synthesis pathways in different microorganisms. However, no microorganisms have been reported yet to produce ethylene glycol naturally. Results: Xylonic acid utilizing microorganisms were screened from natural environments, and an Enterobacter cloacae strain was isolated. The major metabolites of this strain were ethylene glycol and glycolic acid. However, the metabolites were switched to 2,3-bu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…E. cloacae S1 is a strain used for ethylene glycol and glycolic acid production [12]. Here the 2,3butanediol production ability of this strain was tested.…”
Section: Dihydroxyisovaleratementioning
confidence: 99%
See 1 more Smart Citation
“…E. cloacae S1 is a strain used for ethylene glycol and glycolic acid production [12]. Here the 2,3butanediol production ability of this strain was tested.…”
Section: Dihydroxyisovaleratementioning
confidence: 99%
“…E. cloacae S1 is a strain that was isolated from the soil, and this strain produces high levels of ethylene glycol and glycolic acid when cultured with xylonic acid as a carbon source. This strain is a high natural 2,3-butanediol producer and the gene replacement method suitable for this bacterium has been established [12]. The genome of E. cloacae S1 has been sent to GenBank with the accession number of VSZU00000000.…”
mentioning
confidence: 99%
“…All conversion ratios were less than 1, suggesting that a fraction of intermediates of the ethylene glycol and glycolic acid synthesis from xylonic acid might be converted to other products. This is different from ethylene glycol and glycolic acid production by wild-type Enterobacter cloacae, which has a total conversion ratio of nearly 1 mol/mol [17]. It has been mentioned that glycolic acid can be converted to glyoxylate into the glyoxylate cycle [20].…”
Section: The Metabolic Pathway Of Xylonic Acid Catabolism and Ethylene Glycol And Glycolic Acid Synthesismentioning
confidence: 88%
“…However, E. coli might not be the best workhorse for ethylene glycol and glycolic acid production. In our recent research, Enterobacter cloacae has shown higher efficiency in ethylene glycol and glycolic acid production on xylonic acid than the E. coli here [17]. The traditional way of biological utilization of biomass includes the hydrolysis of biomass to monosaccharides, which are further used as a carbon source by microorganisms for their growth and production of various products.…”
Section: The Metabolic Pathway Of Xylonic Acid Catabolism and Ethylene Glycol And Glycolic Acid Synthesismentioning
confidence: 99%